Membangun Kompetensi Critical Thinking Melalui Keterampilan Membaca Di Sekolah Dasar - Anny Wahyu Dwi Jayanti; Taseman; Makrifatul Ilmi; Chelina Aurilia Purwanto; Inayatur Rofi’ah (IAI Al Khoziny Buduran Sidoarjo, 2022)
This study aims to find out how to build critical thinking competence through reading skills in elementary school students. This research is a library research (Library Research). Critical thinking competence or critical thinking is related to the ability to reason, express, analyze, and solve problems. Critical thinking competencies are required to be possessed by students in the 21st century in order to prepare themselves to face global competition. This critical thinking competence can be built through reading skills. In elementary school critical thinking competence is built through several types of reading activities such as intensive reading, scanning reading, comprehension reading, skimming, speed reading, beautiful reading, technical reading and language reading. With a high interest in reading students, it will grow critical thinking competence in students. Students who have the ability to think critically will raise probing questions, have an open mind, and are also able to make logical conclusions based on evidence. Therefore, teachers must strive for students to have good reading skills and high reading interest so that students can have critical thinking competencies.